Sustainable approaches towards green synthesis of TiO2 nanomaterials and their applications in photocatalysis-mediated sensing to monitor environmental pollution - Singh T.; Sharma S.; Singh R.; Pal D.B.; Ahmad I.; Alam M.M.; Singh N.L.; Srivastava M.; Srivastava N. (My University, 2025)
Nanomaterials are gaining enormous interests due to their novel applications that have been explored nearly in every field of our contemporary society. In this scenario, preparations of nanomaterials following green routes have attracted widespread attention in terms of sustainable, reliable, and environmentally friendly practices to produce diverse nanostructures. In this review, we summarize the fundamental processes and mechanisms of green synthesis approaches of TiO2 nanoparticles (NPs). We explore the role of plants and microbes as natural bioresources to prepare TiO2 NPs. Particularly, focus has been made to explore the potential of TiO2-based nanomaterials to design a variety of sensing platforms by exploiting the photocatalysis efficiency under the influence of a light source. These types of sensing are of massive importance for monitoring environmental pollution and therefore for inventing advanced strategies to remediate hazardous pollutants and offer a clean environment. © 2022 John Wiley & Sons Ltd.